(untitled) (Journal of Contemporary Issues in Accounting, 2026)
This study explored the evolution and enterprise adoption of Microservices Architecture (MSA) as a transformative response to the limitations inherent in traditional monolithic and earlier service-oriented systems. Leveraging a systematic mapping study encompassing extensive scholarly and industrial insights, this article synthesizes the technical, operational, and organizational dimensions of microservices implementation across five globally recognized enterprises: Netflix, Amazon, Uber, Alibaba, and Capital One. The findings reveal a consistent and beneficial shift away from monolithic architectures, primarily due to their inherent rigidity, deployment bottlenecks, and limitations in scalability. In contrast, microservices consistently deliver superior modularity, significantly faster time-to-market, enhanced fault isolation, and highly efficient independent service scaling. The diverse case studies highlight unique implementation paths, demonstrating how MSA flexibly adapts to sector-specific needs while consistently yielding improvements in performance, resilience, and business agility. The research concludes that microservices represent a key strategy for fostering technological innovation and achieving long-term strategic goals in the contemporary digital landscape.